Silicon-containing negative plate, lithium ion battery and preparation method
By adding a dispersant containing anchor groups to the negative electrode slurry of lithium-ion batteries, the problem of agglomeration of silicon negative electrode materials during the pulping process is solved, and the circulation performance of the battery is improved.
Patent Information
- Application Number
- CN202411586821.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the small particle size of the silicon negative electrode material leads to agglomeration during the pulping process, resulting in uneven distribution of the silicon negative electrode material and graphite material, affecting the charging and discharging performance and cycling stability of the battery.
The dispersant is added to the negative electrode slurry. The dispersant contains anchoring groups. Through electrostatic repulsion, steric hindrance and strong hydrogen bonding forces, it prevents the agglomeration of silicon particles and improves the consistency of pulping.
Effectively prevent the agglomeration of silicon particles, improve the pulping consistency between silicon materials and graphite negative electrode materials, and improve the circulation performance of the battery.
Smart Images

Figure CN119542344A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of batteries, and in particular relates to a silicon-containing negative electrode sheet and a lithium-ion battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have become an indispensable energy storage method in mobile electronic devices, electric vehicles and energy storage systems due to their high energy density, long life and good charge and discharge performance. With the development of science and technology, the energy density of lithium-ion batteries is increasingly required. Silicon negative electrode materials are widely used to improve the energy density of lithium-ion batteries due to their high theoretical capacity (about 4200mAh / g).
[0003] In recent years, silicon material technology has been continuously developed to improve cycle stability and inhibit volume expansion. In order to reduce silicon anode expansion, the particle size of silicon anode materials is often small; in order to increase battery energy density, the amount of silicon anode materials added is getting higher and higher, which easily leads to agglomeration during the pulping process, resulting in uneven distribution of silicon anode materials and graphite materials.
[0004] In the existing technology, in order to reduce the expansion of silicon negative electrode, the particle size of silicon negative electrode material is often small, which easily causes it to agglomerate during the slurrying process, and the silicon negative electrode material and graphite material are unevenly distributed. The expansion stress is concentrated after lithium is inserted in the silicon negative electrode aggregation position, and the N / P ratio at local points is too high, resulting in local polarization problems. These problems will affect the charge and discharge performance and cycle stability of the battery, and limit the further improvement of the energy density of lithium-ion batteries. Therefore, how to improve the slurrying consistency of silicon-containing negative electrode materials and prevent silicon materials from agglomerating is an important challenge facing current technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a silicon-containing negative electrode sheet and a lithium-ion battery and a preparation method.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A silicon-containing negative electrode sheet comprises a negative electrode current collector and negative electrode active material layers arranged on both sides of the negative electrode current collector; the negative electrode active material layers comprise negative electrode active substances, negative electrode conductive agents, negative electrode binders, and dispersants; the negative electrode active substances comprise graphite negative electrode materials and silicon negative electrode materials; the dispersant comprises anchoring groups; the anchoring groups are one or more of hydroxyl, carboxyl, amino, carbonyl, and amide groups.
[0008] The dispersant is one or more of a polyurethane dispersant, a polyester dispersant, an epoxy dispersant, a polycarboxylate dispersant, and an alkyl alcohol amide dispersant. Preferably, the mass content of the dispersant in the negative electrode active material layer is (0.5-2) %; preferably (1-2) %.
[0009] The mass ratio of the graphite active material, the negative electrode conductive agent, the negative electrode binder, and the dispersant is (80-98): (0-5): (1-5): (0.1-5); preferably (93.5-95): 0.6: 3.9: (0.5-2); more preferably: 94.5: 0.6: 3.9: 1;
[0010] Preferably, the mass ratio of the graphite negative electrode material to the silicon negative electrode material in the graphite active material is (80-98):(2-20); preferably 85:15;
[0011] The graphite negative electrode material is at least one of artificial graphite and natural graphite, preferably artificial graphite;
[0012] The silicon negative electrode material is at least one of silicon monoxide and silicon carbon material;
[0013] The negative electrode conductive agent is at least one of graphene, carbon nanotubes and carbon black; preferably a mixture of carbon black and carbon nanotubes, preferably, the mass ratio of carbon black to carbon nanotubes is 5:1;
[0014] The negative electrode binder is one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, and polyacrylic acid; preferably, a mixture of lithium carboxymethyl cellulose, polyacrylic acid and styrene-butadiene rubber, preferably, the mass ratio of lithium carboxymethyl cellulose, polyacrylic acid and styrene-butadiene rubber is 1:1.9:1;
[0015] The negative electrode current collector is one of copper foil and carbon-coated copper foil.
[0016] The present invention also includes a method for preparing the silicon-containing negative electrode sheet, comprising the following steps: S1: obtaining negative electrode slurry; S2: coating the negative electrode slurry on the surface of the negative electrode collector, heating and drying, and finally obtaining the silicon-containing negative electrode sheet.
[0017] The specific steps of S1 are:
[0018] The first step is to add the binder into deionized water to obtain a binder glue solution, preferably, the solid content of the glue solution is 0.1% to 10%, preferably 1.2%;
[0019] The second step is to add the conductive agent and the dispersant into the adhesive solution and stir evenly to obtain the conductive adhesive;
[0020] The third step is to add the graphite negative electrode material and the silicon negative electrode material to the conductive glue step by step, stir evenly, and then add deionized water to adjust the solid content of the slurry to 35% to 55%, so as to obtain a conductive glue containing the graphite negative electrode material and the silicon negative electrode material;
[0021] The fourth step is to filter the obtained slurry.
[0022] If the binder contains styrene butadiene rubber, the styrene butadiene rubber is added to the conductive glue containing the graphite negative electrode material and the silicon negative electrode material in the third step.
[0023] The first step is to stir at a stirring speed of 100 rpm to 800 rpm for 0.5 h to 24 h;
[0024] The second step is stirring at a stirring speed of 500 rpm to 4000 rpm for 0.5 h to 2.5 h;
[0025] The third step is specifically as follows: after adding the graphite material and the silicon negative electrode material to the conductive glue at the same time, stir at a stirring speed of 100rpm to 800rpm for 15min to 60min, then stir at a stirring speed of 1000rpm to 4000rpm for 0.5h to 4h, add deionized water to adjust the solid content of the conductive glue to 35% to 55%, and then stir at a stirring speed of 1000rpm to 4000rpm for 0.5h to 1.5h to obtain a conductive glue containing graphite material and silicon negative electrode material.
[0026] The fourth step is to stir at a stirring speed of 100 rpm to 800 rpm for 10 min to 30 min; and the slurry is filtered through a 80-200 mesh sieve.
[0027] The present invention also includes a lithium ion battery, comprising the silicon-containing negative electrode sheet, positive electrode sheet and diaphragm.
[0028] The present invention also includes a method for preparing the lithium-ion battery, comprising the following steps: assembling the silicon-containing negative electrode sheet, positive electrode sheet and diaphragm in a stacked form, packaging them into an electrode group with an aluminum-plastic shell, and obtaining a lithium-ion battery through subsequent assembly, liquid injection and formation processes.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The technical solution of the present application is to add a dispersant to the negative electrode slurry, wherein the anchoring group of the dispersant is
[0031] Through electrostatic repulsion, steric hindrance and strong hydrogen bonding forces, silicon particles can be effectively prevented from agglomerating, thereby improving the slurry consistency of silicon materials and graphite negative electrode materials. At the same time, as a preferred form, the technical solution of the present application optimizes the content of the dispersant, and the negative electrode active material particles in the obtained negative electrode sheet are evenly dispersed, and the corresponding battery cycle performance is good. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a scanning electron microscope image of the negative electrode sheet of Example 1 of the present invention;
[0033] Figure 2 This is a scanning electron microscope image of the negative electrode sheet of Example 2;
[0034] Figure 3 This is a scanning electron microscope image of the negative electrode sheet of Example 3;
[0035] Figure 4 This is a scanning electron microscope image of the negative electrode sheet of Example 4;
[0036] Figure 5 is a scanning electron microscope image of the negative electrode sheet of the comparative example;
[0037] Figure 6 The 45°C cycle performance diagram of the batteries of Examples 1 to 4 and the comparative example. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.
[0039] The hydroxy hyperbranched polyester used in Examples 1 to 3 was derived from Bol torn H20 produced by Perstorp, and the alkyl alcohol amide used in Example 4 was derived from 6503 produced by Shandong Jinmei Chemical Company.
[0040] Example 1
[0041] The formula is: negative electrode active material: 95% (artificial graphite A + silicon carbon material B, mass ratio of A:B = 85:15), conductive agent: 0.6% (mass ratio of Super P: single-walled carbon nanotube = 5:1), binder: 3.9% (mass ratio of CMC-L i:PAA: styrene-butadiene rubber = 1:1.9:1), dispersant hydroxyl hyperbranched polyester dispersant: 0.5%.
[0042] Embodiment 1 The specific preparation method of the silicon-containing negative electrode sheet comprises the following steps:
[0043] The first step is to prepare lithium carboxymethyl cellulose CMC glue: 61.9 g of CMC-Li powder is added to deionized water to adjust the solid content of the glue solution to 1.2%, and the mixture is slowly stirred at a speed of 500 rpm for 4 hours to obtain CMC glue;
[0044] The second step is to prepare a conductive adhesive: 31.0 g Super P, 1.548 kg single-walled carbon nanotube conductive agent, 31.0 g terminal hydroxyl hyperbranched polyester dispersant, and 2.941 kg polyacrylic acid binder are added to the CMC adhesive solution, and an appropriate amount of deionized water is added, and the mixture is rapidly stirred at a speed of 4000 rpm for 2.5 hours to obtain a conductive adhesive;
[0045] The third step is to prepare a slurry: 5 kg of artificial graphite and 882.4 g of silicon-carbon material are added step by step to the conductive glue obtained in the second step, and the mixture is slowly stirred at a speed of 500 rpm for 30 min, and then rapidly stirred at a speed of 2500 rpm for 4 h, and deionized water is added to adjust the solid content of the conductive glue to 40%, and then rapidly stirred at a speed of 2000 rpm for 1 h, and 155.6 g of styrene-butadiene rubber binder is continuously added, and the mixture is slowly stirred at a speed of 100 rpm for 20 min to obtain a slurry;
[0046] Step 4: sieving: filtering the obtained slurry through a 100-mesh sieve;
[0047] Step 5: coating: coating the filtered slurry on the surface of the negative electrode current collector of 5 μm thick carbon-coated copper foil to complete the coating process ( Figure 1 SEM images are shown).
[0048] For the present invention, in specific implementation, based on the silicon-containing negative electrode sheet prepared by the present invention, the preparation method for producing a lithium-ion battery is as follows:
[0049] Step 1: rolling the silicon-containing negative electrode sheet of Example 1 according to the compaction density design, and then obtaining the negative electrode sheet through a shearing process;
[0050] Step 2: Assemble the negative electrode sheet, positive electrode sheet and separator obtained in the first step in the form of a stack, package them into an electrode group with an aluminum plastic shell, and obtain a finished battery with a battery capacity of 5Ah through subsequent assembly, injection and formation processes, that is, finally obtain the lithium-ion battery of Example 1.
[0051] Example 2
[0052] The formula is: negative electrode active material: 94.5% (artificial graphite A + silicon carbon material B, mass ratio of A:B = 85:15), conductive agent: 0.6% (mass ratio of Super P: single-walled carbon nanotube = 5:1), binder: 3.9% (mass ratio of CMC-L i:PAA: styrene-butadiene rubber = 1:1.9:1), dispersant hydroxyl hyperbranched polyester dispersant: 1.0%;
[0053] Embodiment 2 The specific preparation method of the silicon-containing negative electrode sheet comprises the following steps:
[0054] The first step is to prepare lithium carboxymethyl cellulose CMC glue: 62.2 g of CMC-Li powder is added to deionized water to adjust the solid content of the glue solution to 1.2%, and the mixture is slowly stirred at a speed of 500 rpm for 4 hours to obtain CMC glue;
[0055] The second step is to prepare a conductive adhesive: 31.1 g Super P, 1.556 kg single-walled carbon nanotube conductive agent, 62.2 g terminal hydroxyl hyperbranched polyester dispersant, and 2.957 kg polyacrylic acid binder are added to the CMC adhesive solution, and an appropriate amount of deionized water is added, and the mixture is rapidly stirred at a speed of 4000 rpm for 2.5 hours to obtain a conductive adhesive;
[0056] The third step is to prepare a slurry: 5 kg of artificial graphite and 882.4 g of silicon-carbon material are added step by step to the conductive glue obtained in the second step, and the mixture is slowly stirred at a speed of 500 rpm for 30 min, and then rapidly stirred at a speed of 2500 rpm for 4 h, and deionized water is added to adjust the solid content of the conductive glue to 40%, and then rapidly stirred at a speed of 2000 rpm for 1 h, and 154.8 g of styrene-butadiene rubber binder is continuously added, and the mixture is slowly stirred at a speed of 100 rpm for 20 min to obtain a slurry;
[0057] Step 4: sieving: filtering the obtained slurry through a 100-mesh sieve;
[0058] Step 5: coating: coating the filtered slurry on the surface of the negative electrode current collector of 5 μm thick carbon-coated copper foil to complete the coating process ( Figure 2 SEM images are shown).
[0059] For the present invention, in specific implementation, the preparation method for producing a lithium-ion battery based on the silicon-containing negative electrode sheet prepared by the present invention is the same as that in Example 1.
[0060] Example 3
[0061] The formula is: negative electrode active material: 93.5% (artificial graphite A + silicon carbon material B, mass ratio of A:B = 85:15), conductive agent: 0.6% (mass ratio of Super P: single-walled carbon nanotube = 5:1), binder: 3.9% (mass ratio of CMC-L i:PAA: styrene-butadiene rubber = 1:1.9:1), dispersant hydroxyl hyperbranched polyester dispersant: 2.0%;
[0062] Embodiment 3 The specific preparation method of the silicon-containing negative electrode sheet comprises the following steps:
[0063] The first step is to prepare carboxymethyl cellulose lithium CMC glue: 62.9g of CMC-Li powder is added to deionized water to adjust the solid content of the glue solution to 1.2%, and the mixture is slowly stirred at a speed of 500 rpm for 4 hours to obtain CMC glue;
[0064] The second step is to prepare a conductive adhesive: 31.5g Super P, 1.573kg single-walled carbon nanotube conductive agent, 125.8g terminal hydroxyl hyperbranched polyester dispersant, and 2.988kg polyacrylic acid binder are added to the CMC adhesive solution, and an appropriate amount of deionized water is added, and the mixture is rapidly stirred at a speed of 4000rpm for 2.5h to obtain a conductive adhesive;
[0065] The third step is to prepare a slurry: 5 kg of artificial graphite and 882.4 g of silicon-carbon material are added step by step to the conductive glue obtained in the second step, and the mixture is slowly stirred at a speed of 500 rpm for 30 min, and then rapidly stirred at a speed of 2500 rpm for 4 h, and deionized water is added to adjust the solid content of the conductive glue to 40%, and then rapidly stirred at a speed of 2000 rpm for 1 h, and 157.3 g of styrene-butadiene rubber binder is continuously added, and the mixture is slowly stirred at a speed of 100 rpm for 20 min to obtain a slurry;
[0066] Step 4: sieving: filtering the obtained slurry through a 100-mesh sieve;
[0067] Step 5: coating: coating the filtered slurry on the surface of the negative electrode current collector of 5 μm thick carbon-coated copper foil to complete the coating process ( Figure 3 SEM images are shown).
[0068] For the present invention, in specific implementation, the preparation method for producing a lithium-ion battery based on the silicon-containing negative electrode sheet prepared by the present invention is the same as that in Example 1.
[0069] Example 4
[0070] The formula is: negative electrode active material: 94.5% (artificial graphite A + silicon carbon material B, A: B mass ratio = 85:15), conductive agent: 0.6% (Super P: single-walled carbon nanotube mass ratio = 5:1), binder: 3.9% (CMC-L i: PAA: styrene-butadiene rubber mass ratio = 1:1.9:1), dispersant alkyl alcohol amide dispersant (same as Example 1, write out the approximate parameters): 1.0%;
[0071] Example 4
[0072] The specific preparation method of the silicon-containing negative electrode sheet comprises the following steps:
[0073] The first step is to prepare carboxymethyl cellulose lithium CMC glue: 62.2g of CMC-Li powder is added to deionized water to adjust the solid content of the glue solution to 1.2%, and the mixture is slowly stirred at a speed of 500 rpm for 4 hours to obtain CMC glue;
[0074] Step 2: prepare conductive adhesive: add 31.1 g Super P, 1.556 kg single-walled carbon nanotube conductive agent, 62.2 g alkyl alcohol amide dispersant, and 2.957 kg polyacrylic acid binder to the CMC adhesive solution, add appropriate amount of deionized water, and stir rapidly at 4000 rpm for 2.5 hours to obtain conductive adhesive;
[0075] The third step is to prepare a slurry: 5 kg of artificial graphite and 882.4 g of silicon-carbon material are added step by step to the conductive glue obtained in the second step, and the mixture is slowly stirred at a speed of 500 rpm for 30 min, and then rapidly stirred at a speed of 2500 rpm for 4 h, and deionized water is added to adjust the solid content of the conductive glue to 40%, and then rapidly stirred at a speed of 2000 rpm for 1 h, and 154.8 g of styrene-butadiene rubber binder is continuously added, and the mixture is slowly stirred at a speed of 100 rpm for 20 min to obtain a slurry;
[0076] Step 4: sieving: filtering the obtained slurry through a 100-mesh sieve;
[0077] Step 5: coating: coating the filtered slurry on the surface of the negative electrode current collector of 5 μm thick carbon-coated copper foil to complete the coating process ( Figure 4 SEM images are shown).
[0078] For the present invention, in specific implementation, the preparation method for producing a lithium-ion battery based on the silicon-containing negative electrode sheet prepared by the present invention is the same as that in Example 1.
[0079] Comparative Example 1
[0080] Comparative Example 1 is a comparative experiment with Example 1, except that no dispersant is added when preparing the conductive glue in the second step of making the negative electrode sheet. The battery preparation method is also consistent with Example 1. The specific formula is: negative electrode active material: 95.5% (artificial graphite A + silicon carbon material B, A:B mass ratio = 85:15), conductive agent: 0.6% (Super P: single-walled carbon nanotube mass ratio = 5:1), binder: 3.9% (CMC-Li:PAA: styrene-butadiene rubber mass ratio = 1:1.9:1). The obtained negative electrode sheet is as follows Figure 5 Shown.
[0081] Figure 6 The 45°C cycle performance diagrams of Examples 1 to 4 and the comparative battery are shown. The results show that in the comparative battery without using a dispersant, the silicon negative electrode particles agglomerate and decay rapidly during the cycle; Examples 1 to 3 use dispersants of different contents. When the amount of dispersant is 0.5%, there is a situation of uneven local dispersion of silicon particles; when the amount of dispersant is adjusted to ≥1%, the dispersion effect is good and the silicon negative electrode particles do not agglomerate significantly; but when the amount of dispersant is too much (>2%), the battery impedance increases, resulting in a decrease in the battery cycle performance. Examples 2 and 4 use different types of dispersants, and both achieve good dispersion effects and excellent battery cycle performance.
[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A silicon-containing negative electrode sheet, characterized in that: It includes a negative electrode current collector and a negative electrode active material layer arranged on both sides of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active substance, a negative electrode conductive agent, a negative electrode binder, and a dispersant; the negative electrode active substance includes a graphite negative electrode material and a silicon negative electrode material; the dispersant includes an anchoring group; the anchoring group is one or more of a hydroxyl group, a carboxyl group, an amino group, a carbonyl group, and an amide group.
2. The silicon-containing negative electrode sheet according to claim 1, characterized in that: The dispersant is one or more of a polyurethane dispersant, a polyester dispersant, an epoxy dispersant, a polycarboxylate dispersant, and an alkylolamide dispersant; preferably, the mass content of the dispersant in the negative electrode active material layer is (0.5-2)%, preferably (1-2)%.
3. The silicon-containing negative electrode sheet according to claim 1, characterized in that: The mass ratio of the graphite active material, the negative electrode conductive agent, the negative electrode binder, and the dispersant is (80-98): (0-5): (1-5): (0.1-5); preferably (93.5-95): 0.6: 3.9: (0.5-2); more preferably: 94.5: 0.6: 3.9: 1; Preferably, the mass ratio of the graphite negative electrode material to the silicon negative electrode material in the graphite active material is (80-98):(2-20); preferably 85:
15.
4. The silicon-containing negative electrode sheet according to claim 1, characterized in that: The graphite negative electrode material is at least one of artificial graphite and natural graphite, preferably artificial graphite; The silicon negative electrode material is at least one of silicon monoxide and silicon carbon material; The negative electrode conductive agent is at least one of graphene, carbon nanotubes and carbon black; preferably a mixture of carbon black and carbon nanotubes, preferably, the mass ratio of carbon black to carbon nanotubes is 5:1; The negative electrode binder is one or more of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, and polyacrylic acid; preferably, a mixture of lithium carboxymethyl cellulose, polyacrylic acid and styrene-butadiene rubber, preferably, the mass ratio of lithium carboxymethyl cellulose, polyacrylic acid and styrene-butadiene rubber is 1:1.9:1; The negative electrode current collector is one of copper foil and carbon-coated copper foil.
5. A method for preparing a silicon-containing negative electrode sheet according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1: obtaining negative electrode slurry; S2: coating the negative electrode slurry on the surface of the negative electrode current collector, heating and drying, and finally obtaining a silicon-containing negative electrode sheet.
6. The method for preparing a silicon-containing negative electrode sheet according to claim 5, characterized in that: The specific steps of S1 are: The first step is to add the binder into deionized water to obtain a binder glue solution, preferably, the solid content of the glue solution is 0.1% to 10%, preferably 1.2%; The second step is to add the conductive agent and the dispersant into the adhesive solution and stir evenly to obtain the conductive adhesive; The third step is to add the graphite negative electrode material and the silicon negative electrode material to the conductive glue step by step, stir evenly, and then add deionized water to adjust the solid content of the slurry to 35% to 55%, so as to obtain a conductive glue containing the graphite negative electrode material and the silicon negative electrode material; The fourth step is to filter the obtained slurry.
7. The preparation method according to claim 6, characterized in that: If the binder contains styrene butadiene rubber, the styrene butadiene rubber is added to the conductive glue containing the graphite negative electrode material and the silicon negative electrode material in the third step.
8. The method for preparing a silicon-containing negative electrode sheet according to claim 6, characterized in that: The first step is to stir at a stirring speed of 100 rpm to 800 rpm for 0.5 h to 24 h; The second step is stirring at a stirring speed of 500 rpm to 4000 rpm for 0.5 h to 2.5 h; The third step is specifically as follows: after adding the graphite material and the silicon negative electrode material to the conductive glue at the same time, stir at a stirring speed of 100rpm to 800rpm for 15min to 60min, then stir at a stirring speed of 1000rpm to 4000rpm for 0.5h to 4h, add deionized water to adjust the solid content of the conductive glue to 35% to 55%, and then stir at a stirring speed of 1000rpm to 4000rpm for 0.5h to 1.5h to obtain a conductive glue containing graphite material and silicon negative electrode material. The fourth step is to stir at a stirring speed of 100 rpm to 800 rpm for 10 min to 30 min; and the slurry is filtered through a 80-200 mesh sieve.
9. A lithium ion battery, characterized in that: It comprises the silicon-containing negative electrode sheet, positive electrode sheet and separator as described in any one of claims 1 to 4.
10. A method for preparing a lithium ion battery according to claim 9, characterized in that: The method comprises the following steps: assembling the silicon-containing negative electrode sheet, positive electrode sheet and diaphragm in the form of stacked sheets, packaging them into an electrode group with an aluminum-plastic shell, and obtaining a lithium-ion battery through subsequent assembly, liquid injection and formation processes.